A comparative study on portfolio performance of main board and second board companies - Gobi Nath, A/L D. Marimuthu (Universiti Malaysia Sarawak, (UNIMAS), 2002)
This paper empirically investigates the technical efficiency in Malaysian Domestic Commercial Banks in both scenarios : pre and post merger period. A non-parametric method of Data Envelopment Analysis (DEA) has been used to arrive at the efficiency scores. Banks in the sample were generally found to have inconsistent level of efficiency for the period under study